2018
DOI: 10.1152/jn.00582.2017
|View full text |Cite
|
Sign up to set email alerts
|

Case Studies in Neuroscience: A dissociation of balance and posture demonstrated by camptocormia

Abstract: Upright stance in humans requires an intricate exchange between the neural mechanisms that control balance and those that control posture; however, the distinction between these control systems is hard to discern in healthy subjects. By studying balance and postural control of a participant with camptocormia - an involuntary flexion of the trunk during standing that resolves when supine - a divergence between balance and postural control was revealed. A kinematic and kinetic investigation of standing and walki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…More detailed evidence comes from a case study of a patient with camptocormia, and condition where posture becomes 'bent over' whilst standing [86]. This study found that whilst posture was perturbed by camptocormia, balance remained intact, dissociating the balance component from particular states and trajectories of posture.…”
Section: What Happens Next? Post-buoyancy Adaptation and Sensorimotor...mentioning
confidence: 99%
“…More detailed evidence comes from a case study of a patient with camptocormia, and condition where posture becomes 'bent over' whilst standing [86]. This study found that whilst posture was perturbed by camptocormia, balance remained intact, dissociating the balance component from particular states and trajectories of posture.…”
Section: What Happens Next? Post-buoyancy Adaptation and Sensorimotor...mentioning
confidence: 99%
“…If this distinct challenge is met by a distinct homeostatic response, one would expect to observe a dissociation between the pure 'postural control' system (arranging body and limbs), and the 'antigravity balance system' (supporting the weight of body and limbs). There is some evidence for such dissociation from a case study of a patient with camptocormia, a condition where posture becomes bent over whilst standing [112].…”
Section: 𝑀𝑀mentioning
confidence: 99%
“…If this distinct challenge is met by a distinct homeostatic response, one would expect to observe a dissociation between the pure 'postural control' system (arranging body and limbs), and the 'antigravity balance system' (supporting the weight of body and limbs). There is some evidence for such dissociation from a case study of a patient with camptocormia, a condition where posture becomes bent over whilst standing [113].…”
Section: 𝑀𝑀mentioning
confidence: 99%